1992
DOI: 10.1002/bdd.2510130906
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐differences in the disposition of substituted benzamides: Pharmacokinetics of a gastroprokinetic agent (4‐amino‐5‐chloro‐2‐[2‐(methylsulfinyl) ethoxy]‐N‐[2‐(diethylamino)ethyl] benzamide hydrochloride) (ML‐1035) in male and female New Zealand white rabbits

Abstract: The disposition of 4-amino-5-chloro-2-[2-(methylsulfinyl)ethoxy]-N- [2-(diethylamino)ethyl] benzamide hydrochloride (ML-1035) following intravenous (10 mg kg-1) and oral (200 mg kg-1) dosing was investigated in male and female New Zealand white rabbits. After intravenous dosing ML-1035 was eliminated with a half-life of 1.45 +/- 0.49 h in males and 0.79 +/- 0.08 h in females. Volume of distribution at steady-state was 2.08 +/- 0.98 l kg-1 in males and 9.11 +/- 5.86 l kg-1 in females. Clearance averaged 2.99 +/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…14 Metoclopramide is conjugated with sulfuronic-and/or glucuronic acid, however, the major urinary metabolite is metoclopramide-N-4-sulfate. 41,45,46 According to Rao et al 48 pharmacokinetic parameters are significantly different between males and females. No results of in vitro transport studies in Caco-2 or other cell culture systems could be identified and no information about the intestinal absorption mechanism of the drug substance was found.…”
Section: Pharmacokinetic Properties Absorption and Permeabilitymentioning
confidence: 99%
“…14 Metoclopramide is conjugated with sulfuronic-and/or glucuronic acid, however, the major urinary metabolite is metoclopramide-N-4-sulfate. 41,45,46 According to Rao et al 48 pharmacokinetic parameters are significantly different between males and females. No results of in vitro transport studies in Caco-2 or other cell culture systems could be identified and no information about the intestinal absorption mechanism of the drug substance was found.…”
Section: Pharmacokinetic Properties Absorption and Permeabilitymentioning
confidence: 99%